Dynamics of Ambidextrous Leadership in Fostering Innovative Work Behaviour and Employee Performance - Divasa Fatikhatul Laeli; Fatmah Bagis; Naelati Tubastuvi; Meydy Fauziridwan (Universitas Airlangga, 2026)
Dynamic changes in the healthcare sector require organizations to adopt a leadership style that is capable of encouraging innovation while maintaining work stability. This study aims to examine the effect of ambidextrous leadership, consisting of opening leadership behavior and closing leadership behavior, on innovative work behavior and employee performance, and to analyze the mediating role of innovative work behavior. The study used a quantitative approach with a population of 524 employees with a final sample of 235 respondents from three health institutions in Pemalang Regency. Data were collected through an online questionnaire and analyzed using SEM-PLS. The results of the study show that opening leadership behavior and closing leadership behavior do not have a direct effect on employee performance. However, both leadership behaviors had a positive and significant effect on innovative work behavior. In addition, innovative work behavior was proven to significantly influence employee performance and mediate the relationship between opening leadership behavior and closing leadership behavior with employee performance. These findings confirm that innovation is a key mechanism in converting the influence of ambidextrous leadership into improved employee performance. The practical implications of this study emphasize the importance of cultivating an innovative work culture and the role of leaders in balancing freedom to explore with procedural control to improve work effectiveness in healthcare institutions. procedural control to improve work effectiveness in healthcare institutions.